PENGARUH KEBIJAKAN HUTANG DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PROPERTY AND REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2015 - Sufitri Muwarni; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to examine partially and simultaneously the influence of Debt Policy and the disclosure of Profitability on the value of the company. Where the independent variable in this study is Debt Policy and the disclosure of Profitability while the dependent variable is the value of the company. The sample used is secondary data derived from the financial statements of the Property and Real Estate on the Indonesia Stock Exchange (BEI) for the period 2011 to 2015.This study uses secondary data from the company's financial statements. Samples and sampling using purposive sampling technique. Data analysis using simple and multiple linear regression analysis, t test, F test, and determination coefficient test with SPSS 20. The results of this study indicate that Debt Policy variables partially (t test) affect the value of the company, while variable Profitability pasrial (t test) does not affect the value of the company in the company Property and Real Estate on the Indonesia Stock Exchange. Simultaneous test results (F) show no effect of debt and profitability policy variables on firm value in property and real estate companies listed on the Indonesia Stock Exchange.Keywords: Debt Policy, Profitability and corporate value